Pengaruh ESG Disclosure Terhadap Firm Value dengan Leverage dan Firm Size Sebagai Variabel Kontrol - Adis Silvi Amalia; Ni Nyoman Alit Triani (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research aims to analyze the influence of Environmental, Social, and Governance (ESG) Disclosure on Firm Value with Leverage and Firm Size as control variables in companies listed on the Indonesia Stock Exchange in 2024. The research uses a quantitative approach with a causality design. The research sample consisted of 288 companies selected using purposive sampling techniques. Secondary data was collected through documentation techniques in the company's annual report and sustainability report. ESG Disclosure is measured based on Global Reporting Initiative (GRI) indicators, Firm Value is proxied using Tobin's Q, Leverage uses Debt to Asset Ratio (DAR), while Firm Size is measured using the natural logarithm of total assets. Data were analyzed using multiple linear regression analysis. The research results show that ESG Disclosure and Firm Size have a positive and significant effect on Firm Value, while Leverage has a negative and significant effect. These findings indicate that companies with higher levels of ESG disclosure tend to obtain better market valuations, while high levels of debt can reduce company value. Simultaneously, the three variables have a significant effect on Firm Value. The research results confirm the importance of ESG transparency as a strategy to increase investor confidence and company value.